2011
DOI: 10.1007/s10734-011-9474-3
|View full text |Cite
|
Sign up to set email alerts
|

A gendered point of view on the challenges of women academics in The People’s Republic of China

Abstract: The authors conducted a qualitative study of women's experiences as faculty members at Northern Research University, a pseudonym for a top 40 university in The People's Republic of China. Based on 27 semi-structured interviews with women (15) and men (12), and drawing from feminist standpoint theory and symbolic interactionism, the authors identified four key findings that highlight serious barriers confronting Chinese women faculty. They describe these as: (1) working double time, (2) the glass ceiling, (3) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 26 publications
1
35
0
1
Order By: Relevance
“…Women who are lower grade managers and professionals were also more likely to report poorer self-rated health after controlling other factors. This may be due to external factors such as work and social pressures and limited opportunity for women to seek promotion to the highest levels [ 61 , 62 ]. Our data showed that a greater proportion of men were higher grade managers or professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Women who are lower grade managers and professionals were also more likely to report poorer self-rated health after controlling other factors. This may be due to external factors such as work and social pressures and limited opportunity for women to seek promotion to the highest levels [ 61 , 62 ]. Our data showed that a greater proportion of men were higher grade managers or professionals.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the findings of these studies indicate that the diversity in men's experiences with and perceptions of gender inequalities cannot be ignored (Bird, ; Ecklund et al, ; Rhoads & Gu, ). Ecklund et al () reveal that the differences between men's and women's attitudes cannot be simplified to a dichotomy of individualistic versus structural explanations.…”
Section: Men and Gendered Structures Of Academic Stem: Attitudes And mentioning
confidence: 98%
“…In the vast literature on gender inequalities in academic STEM, few studies have focused on faculty attitudes towards challenges facing women (Ecklund, Lincoln, & Tansey, ), and even fewer have focused specifically on men's attitudes. Available studies that have included men in their analysis are in agreement that men are less likely than women to recognize systemic barriers against women's advancement in STEM (Bird, ; Ecklund et al, ; Rhoads & Gu, ). These studies find that men typically see women's challenges as outcomes of women's personal situations and preferences rather than of institutional arrangements (Rhoads & Gu, ).…”
Section: Men and Gendered Structures Of Academic Stem: Attitudes And mentioning
confidence: 98%
See 1 more Smart Citation
“…In their study of the experiences of female academics in China, Rhoads and Gu () highlighted the ongoing challenges women face, especially in terms of failing to progress to the most senior levels of the professorate. With regard to rankings and opportunities for women, Rhoads and Gu () raised this important question: “What impact might such rankings have on the betterment of opportunities for academic women, at a global level, if they actually required universities to report gender data and then used such data in their complex ranking schemas?” (p. 747). Implementing such measures does not seem overwhelmingly difficult, although one might reasonably question the institutional commitment to advancing such an idea.…”
Section: Advancing a Social Justice Visionmentioning
confidence: 99%